BUDAYA KERJA DAN MOTIVASI PEGAWAI PADA KANTOR PERWAKILAN BKKBN PROVINSI MALUKU - LAURENS, SAMSONS (JURNAL BADATI, 2020)
This study aims to analyze; (1) employee work culture, (2) employee work motivation,(3) work culture relationship with employee motivation. The population of this study were allemployees at the Maluku Provincial BKKBN Representative Office, amounting to 115 people.The number of samples is based on the table developed by Issac and Michael, ie if thepopulation is 115 people, with an error rate of 5%, then the total sample of 83 people isdetermined at randomly simple. The analysis used is chi square analysis. The results showedthat; (1) Work culture with attitude indicators is a happy, sincere and responsible attitudetowards work and shows friendly and polite attitude; (2) High employee motivation is shownby employees working earnestly and responsibly and having motives for meeting economicneeds, improving welfare, improving careers and rewards, and having clear hopes and desirestowards increasing incentives and (3) Cultural variables work which includes attitudes,behavior and discipline is positively related to employee motivation in the form of motives,hopes, needs and incentives.